2019
DOI: 10.1039/c8ra10163a
|View full text |Cite
|
Sign up to set email alerts
|

In silicopost-SELEX screening and experimental characterizations for acquisition of high affinity DNA aptamers against carcinoembryonic antigen

Abstract: High affinity DNA aptamers against carcinoembryonic antigen were selected and verified by using an in silico approach and experimental characterizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…3D structure prediction methods for RNAs are commonly used for DNA structure prediction. RNAComposer could be used to generate 3D structures of RNAs and then transformed to DNA structures [ 44 , 45 ]. For example, Iman et al introduced a workflow for predicting 3D structures for DNA aptamers [ 20 ].…”
Section: Aptamer Affinity Prediction Through Structural Informatiomentioning
confidence: 99%
“…3D structure prediction methods for RNAs are commonly used for DNA structure prediction. RNAComposer could be used to generate 3D structures of RNAs and then transformed to DNA structures [ 44 , 45 ]. For example, Iman et al introduced a workflow for predicting 3D structures for DNA aptamers [ 20 ].…”
Section: Aptamer Affinity Prediction Through Structural Informatiomentioning
confidence: 99%
“…DNA aptamers were designed against carcinoembryonic antigen (CEA; PDB ID 2QSQ) [ 43 ]. A DNA mutant library was developed via nucleobase substitution or addition to the parent (P) sequence (5′-ATACCAGCTTATTCAATT-3′).…”
Section: Proteins As Targets Of Aptamer Designmentioning
confidence: 99%
“…The B1-4, as a parent aptamer, was randomly mutated through an in silico base mutagenesis program designed by our team. The number of mutants in this study was about 1000 in each round, much higher than before [ 9 ]. The higher number of mutants means more possibilities of obtaining the sequence with better performance.…”
Section: Methodsmentioning
confidence: 59%
“…Hsieh et al successfully found one new sequence that could produce a relatively superior binding reaction with a prostate-specific antigen based on the known aptamers [ 8 ]. Wang et al identified two aptamer mutants against the carcinoembryonic antigen exhibiting significantly high binding ability [ 9 ]. Thus far, the in silico post-SELEX strategy has been performed to engineer high-affinity aptamers for several targets.…”
Section: Introductionmentioning
confidence: 99%